The Influence of RPBL on Visual Thinking and Mathematical Problem Solving Skills on Plane Structure Material - Santi Oktafenti; Cut Latifah Zahari (Universitas Muria Kudus, 2026)
This study used Realistic Problem-Based Learning (RPBL) on plane geometry material, namely plane figures, to improve students' visual thinking and mathematical problem solving. Geometry Project-Based Learning encourages visual and mathematical problem solving. This quasi-experimental quantitative study used a non-equivalent control group. All ninth-grade students of SMP Harapan 3 Medan participated in the survey. Class IX D (28 students) was the experimental class, and class IX E (29 students) was the control class. Pemilihan subjek dilakukan secara purposive sampling. The instrument used was a written test of visual thinking and mathematical problem-solving abilities. Visual reasoning and numerical problem solving were examined before and after the intervention. N-Gain and statistical testing measured student improvement. Visual reasoning increased from 58.21 to 82.36 in the experimental class. Mathematics problem solving scores increased from 56.47 to 81.12. A significance value of 0.000 <0.05 indicates a significant difference between the experimental and control classes in hypothesis testing. N-Gain found that experimental students improved slightly more than control students. This indicates that RPBL improves students' numeracy and visual abilities. This indicates that RPBL improves students' visual thinking and mathematical problem-solving skills. This research demonstrates that RPBL can be an innovative, contextual, and alternative arithmetic learning strategy.